Technology push strategies and their consequences on sustainable development in manufacturing industries. (14th June 2019) - Singla, Anuj; Ahuja, I.P.S.; Sethi, A.P.S.
The objective behind the review is to have an insight of technology push (TP) activities to escalate the essential capabilities in manufacturing ventures and analyse the experiences of the developed and developing countries. Themes and relevant articles have been identified from the various journals and linked with issues related to technology push for sustainable development in manufacturing industries. The study reveals that adjustment of viable TP strategies may help towards reckoning key skills in the framework of a company. In addition to this, the review emphasises that the TP strategies has significant impact on the sustainable development of the manufacturing industries. It has been observed that the role of TP in manufacturing companies has not been much reported. A synthesis can be established with satisfaction levels of TP strategies, which may help to secure concrete objectives and interests of an organisation. The paper reviews various attributes of TP through a number of publications in this field.